Исследование реакции гомолитического разрыва связи C-N в алкилвердазилах; СХС-2025 - Ковальская Е. С. Екатерина Сергеевна; Курцевич А. Е.; Воткина Д. Е. Дарья Евгеньевна; Валиев Р. Р. Рашид Ринатович; Постников П. С. Павел Сергеевич; Петунин П. В. Павел Васильевич (2025, 2025)
Текстовый файл